THE ROLE OF WHATSAPP IN TEACHING VOCABULARY TO THE STAFFS OF UMBUL PONGGOK KLATEN - Lia Ardiana Safitri (JURNAL ILMIAH EDUNOMIKA, 2021)
This study was conducted with the aim of knowing the significant role of WhatsApp in teaching vocabulary, especially staff learning achievement which was limited to vocabulary achievement as measured by a vocabulary test at Umbul Ponggok Klaten. Participants in this study amounted to 30 people consisting of 15 men and 15 women. All participants will learn English as a foreign language using WhatsApp to learn new vocabulary items via their mobile, tablet or laptop. Participants' English level will be measured. Random sampling procedure was carried out. To carry out the research, a true experimental design was used. The participants were assigned to two experimental and control groups. The assessment instrument in this study used a pre-test and post-test. The results showed that the use of the WhatsApp application in teaching vocabulary to the Umbul Ponggok Klaten staff was able to improve the achievement of new English vocabulary mastery of the Umbul Ponggok Klaten staff which was getting better.